Feasibility and Safety of Outpatient Parenteral Antimicrobial Therapy in Conjunction With Addiction Treatment for People Who Inject Drugs - Price, Christin N (J Infect Dis, 2020)
BACKGROUND: Research is limited on combining outpatient parenteral antimicrobial therapy (OPAT) with addiction treatment for people who inject drugs (PWID) with serious infections. METHODS: This is a retrospective study of PWID (n = 68) requiring intravenous antibiotics evaluated for suitability for our OPAT program with concurrent addiction treatment. RESULTS: Most common infections were bacteremia and/or endocarditis (73.5%), bone and/or joint infections (32.4%), and epidural abscess (22.1%). Of the 20 patients (29.4%) who qualified, 100.0% completed the course of antibiotics, 30.0% experienced a 30-day readmission, and 15.0% relapsed. No overdoses, deaths, or peripherally inserted central catheter-line complications were reported. CONCLUSIONS: Outpatient parenteral antimicrobial therapy with addiction treatment may be feasible and safe for PWID with serious infections.